Anmerkungen zu mittelassyrischen Texten. 7 - Freydank, Helmut (Altorientalische Forschungen, 2011)
1. There are clear indications that two eponyms recently dated to the reign of Tukultī-Ninurta I in fact held office under an earlier king. 2./3. Three loan contracts and further administrative documents from Aššur are discussed in detail in light of the cultic requirements implied by them. 4. A recently proposed argument for dating two administrative records from Kār-Tukultī-Ninurta is shown not to be valid.